The importance of ethics for business growth and development in VUCA environments - SÁNCHEZ RODRÍGUEZ, Salvador (2024)
The present work is a literature review that seeks to relate decision making in VUCA environments (abbreviation for volatility, uncertainty, complexity and ambiguity); with the ethics of entrepreneurs and businessmen for the growth and development of companies. As a starting point we explore the reasons for distinguishing the entrepreneur from the businessman, both roles coexist within companies and although it can and is normally the same person, the rationality used by one and the other is not the same. In a second moment, a review of what it means to develop business activities in VUCA environments is presented. Ending this exploration with a recount of what ethics means and its importance that the decisions that involve organizations are within a beneficial ethics for the actors of the system, as conclusions, ethics is of great relevance for the permanence in the market, achieving benefits for the ecosystem in which it carries out its activities.